COVID-19: Not a Positive Test Result, but a Positive Outlook - Yoo, Jae; Mercer, Nathaniel (International Journal of Medical Students, 2021)
Turning the page into the new year was a relief for everyone. Indeed, it was a year of loss, destruction, and unrest. But beyond all this, we can still reflect back on the tumultuous year that is 2020 and catch sight of all the good that occurred. More so, it was a year of reconnecting with lost time, friends and family. Collectively, we were able to reinvent ourselves by slowing down and appreciating what we have. As a society, we grew together - hand in hand - to battle the prejudice that still remains deeply rooted in our country. As such, we can continue to make stride for a more free and safe world for future generations. COVID-19, a virus that crippled the world, opened the world’s eyes to the atrocities that occur on a daily basis. Despite the devastating images of overworked healthcare professionals throughout the pandemic, it is encouraging that future generations have not lost faith in medicine, and are still invigorated to pursue their passion.